T4 apoptosis in the acute phase of SARS-CoV-2 infection predicts long COVID - Cezar, Renaud; Kundura, Lucy; André, Sonia; Lozano, Claire; Vincent, Thierry; Muller, Laurent; Lefrant, Jean-Yves; Roger, Claire; Claret, Pierre-Géraud; Duvnjak, Sandra; Loubet, Paul; Sotto, Albert; et al. (Frontiers in Immunology, 2024)
Background: As about 10% of patients with COVID-19 present sequelae, it is important to better understand the physiopathology of so-called long COVID. Method: To this aim, we recruited 29 patients hospitalized for SARS-CoV-2 infection and, by Luminex ® , quantified 19 soluble factors in their plasma and in the supernatant of their peripheral blood mononuclear cells, including inflammatory and anti-inflammatory cytokines and chemokines, Th1/Th2/Th17 cytokines, and endothelium activation markers. We also measured their T4, T8 and NK differentiation, activation, exhaustion and senescence, T cell apoptosis, and monocyte subpopulations by flow cytometry. We compared these markers between participants who developed long COVID or not one year later. Results: None of these markers was predictive for sequelae, except programmed T4 cell death. T4 lymphocytes from participants who later presented long COVID were more apoptotic in culture than those of sequelae-free participants at Month 12 (36.9 ± 14.7 vs. 24.2 ± 9.0 %, p = 0.016). Conclusions: Our observation raises the hypothesis that T4 cell death during the acute phase of SARS-CoV-2 infection might pave the way for long COVID. Mechanistically, T4 lymphopenia might favor phenomena that could cause sequelae, including SARS-CoV-2 persistence, reactivation of other viruses, autoimmunity and immune dysregulation. In this scenario, inhibiting T cell apoptosis, for instance, by caspase inhibitors, could prevent long COVID.